Inter-Religious Relations and Methodologi Issues - Abdul Syukur (Jounal Nyanadassana, 2022)
Every religion teaches its followers to live peacefully and harmoniously with others, both the same and different religion followers. However, the fact shows that relations among religious people are often to be problematical. This is not only because of differences between religions in doctrines and practices but also because of different interpretations (sects) and organizations. This religious conflict obviously will harm the religious people themselves. As humanity, religious people want to live together harmoniously with others, both fellow religion, and different religions, because they live on the same earth. This article will discuss how are the inter-religious relationships related to methodological problems in the field of religious studies. Methodologically, Comparative Religion that developed in the early time it studied religions from a theological perspective that is looking at the other religions from their own. So, what happened was the pokrol bambu attitude, raising his religion and demeaning on another. This method is not good for students who study religions, particularly for Indonesians who are multi-religious, because it will only look at his/her religion as superior whereas another as inferior. Wilfred Cantwell Smith, on the other hand, offers a method that is personalizing religion as a way of studying religions. Religion should not be seen only as a set of fixed doctrines and ready-made. The problem of religion is essentially a human problem in which the adherents of each religion always understand, experience and realize their religious beliefs and practices in daily life. Therefore, religion is always new every day. This method or approach requires students to study other religions through the perspective of the people who embraced it, so that, biased interpretation can be avoided. This method requires students to come and have a dialogue with the religious followers concerned.